Is vessel narrowing secondary to pediatric deep neck space infections of clinical significance?. (October 2019) - Carroll, William; Van Beck, Jenna; Roby, Brianne
Abstract: Introduction: Pediatric deep neck space infections (DNSI) may cause internal jugular vein and/or carotid artery narrowing. Radiologists and otolaryngologists are often queried by emergency room providers and pediatricians with regards to the clinical significance when this radiographic finding is noted. There are often questions raised about need for further imaging, anticoagulation and overall management strategy. There is limited data to support our answers to these questions. This study investigated the clinical significance of vessel narrowing of the internal jugular vein and carotid artery in the setting of DNSI in children. Methods: 208 patients over a 10 year period were reviewed in retrospective fashion. CT scans reports were evaluated for vessel narrowing, and clinical outcomes were analyzed. Results: This study found that nearly half (44.7%, 93 of 208) of pediatric DNSIs reviewed showed evidence of either carotid and/or internal jugular vein narrowing. There was no significant difference in vascular complications in those with vessel narrowing and those without (p = 0.09). There were no observed neurologic complications in either group. Conclusions: Vessel narrowing is a very common finding in pediatric DNSI. Vascular complications are very rare, and importantly no patients had neurologic complications in either group (vessel narrowing or not). We found no evidence to support more aggressive surgical management, getting further imaging, starting anticoagulation, nor changing overall management strategy for patients based solely to the finding of vessel narrowing in DNSI.